DAMPAK IMPLEMENTASI PROGRAM REFORMA AGRARIA TERHADAP PENDAPATAN PETANI DI KECAMATAN CIPARI KABUPATEN CILACAP TAHUN 2010 - Rahmat Iriyanto Sugeng (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
Land is the backbone of the income of farmers in the district Cipari Cilacap because the majority of the population are farmers. Ownership, control, processing and structuring is a key struggle for farmers. The implementation of the agrarian reform program has been implemented in the district Cipari Cilacap with land redistribution kegiatanya is ex-leasehold (HGU) PT Rumpun Sari Antan (PT RSA) to the farm workers who are entitled to the land in accordance with the provisions that have been determined. Agrarian reform program has an impact on the economy of local communities, especially the impact on farmers’ incomes quickly became the target of the agrarian reform program. The purpose of this study was to determine how the implementation of the agrarian reform program and its impact on farm workers incomes in Sub Ciapari Cilacap. The study population amounted to 5141 people, 100 people sempel techniques Proportional Area Cluster Random Sampling, research variables are income variables as the dependent variable and the variable land ownership as independent variables. Methods of analysis using descriptive statistical analysis and test samples t test. The results showed in the table of statistics for paired samples drawn sample of 100 randomly obtained an average income of farmers in the district Cipari Cilacap before the agrarian reform policy amounted to Rp.940, 050 while the average income of farmers after the agrarian reform policy amounted to Rp.946, 250. Both the average is different from that H0 is rejected, which means that there is a difference between before and after the policy of agrarian reform. From these results it can be seen that there is a change in the income of farmers before and after the policy of the agrarian reform program in the District Cipari Cilacap.Output District paired samples correlation addressed the correlation results between the two samples. The correlation is shown with the number 0909 with a probability value = 0.000 <0.05 = 5%, which means the relationship (correlation) between the income of farmers before and after the agrarian reform policy was a close relationship. From the table above paired sample test can be known sig (2-tailed) = 0.000 <0.05 = 5% so H0 is rejected so it can be concluded that there are differences in Patani earnings before and after the government’s agrarian reform policy.